2014
DOI: 10.1073/pnas.1322280111
|View full text |Cite
|
Sign up to set email alerts
|

Urban adaptation can roll back warming of emerging megapolitan regions

Abstract: Modeling results incorporating several distinct urban expansion futures for the United States in 2100 show that, in the absence of any adaptive urban design, megapolitan expansion, alone and separate from greenhouse gas-induced forcing, can be expected to raise near-surface temperatures 1-2°C not just at the scale of individual cities but over large regional swaths of the country. This warming is a significant fraction of the 21st century greenhouse gas-induced climate change simulated by global climate models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
261
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 432 publications
(272 citation statements)
references
References 28 publications
4
261
1
6
Order By: Relevance
“…Consequently, Africa will make up an increasingly larger fraction of total urban land (Güneralp & Seto, 2013). Such recognition of anticipated urban expansion has implications for prioritization of strategies guiding sustainable urban development (i.e., retrofitting relative to planning of future cities), which have largely focused on reduction of greenhouse gas emissions and on land-based solutions such as green and cool roofs (Georgescu et al, 2014;Sailor, 2008), increased vegetation fraction (Krayenhoff et al, 2014;Middel et al, 2015), and local engineering-based solutions (Meggers et al, 2016). In addition to potentially beneficial aspects of landscape configuration (Connors et al, 2013), deployment of natural capital within built environments may provide considerable additional human and environmental cobenefits.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Africa will make up an increasingly larger fraction of total urban land (Güneralp & Seto, 2013). Such recognition of anticipated urban expansion has implications for prioritization of strategies guiding sustainable urban development (i.e., retrofitting relative to planning of future cities), which have largely focused on reduction of greenhouse gas emissions and on land-based solutions such as green and cool roofs (Georgescu et al, 2014;Sailor, 2008), increased vegetation fraction (Krayenhoff et al, 2014;Middel et al, 2015), and local engineering-based solutions (Meggers et al, 2016). In addition to potentially beneficial aspects of landscape configuration (Connors et al, 2013), deployment of natural capital within built environments may provide considerable additional human and environmental cobenefits.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reveal that the large-scale deployment of roofing technologies is an effective means of reducing energy consumption (e.g., Akbari et al 2009;Oleson et al 2010;Menon et al 2010;Salamanca et al 2012a;Cotana et al 2014;Georgescu et al 2014). Cool roofs, by virtue of increased reflectivities, absorb less incoming shortwave radiation than dark roofs, thereby promoting a lower skin temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In wintertime, the potential penalty associated with cool roofs is in general outweighed by the summer benefit and can be annulled if the roofs are typically covered with snow during the cold season (Bretz and Akbari 1997). However, energy savings are more limited for areas that do not have extensive wintertime snow pack, such as the Mid-Atlantic states of the USA (e.g., Georgescu et al 2014). Various studies have documented the direct benefits of large-scale cool roof deployment in urban areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"If we don't have that, then we don't have precipitation, " says Georgescu. In a modelling study 7 , he found that if cool roofs were widely implemented in urban areas from Florida to the northeastern United States, daily summertime precipitation could decrease by 2-4 millimetres by 2100.…”
Section: Downsides Of Coolmentioning
confidence: 99%